ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN DAN PRESEPSI HARGA TERHADAP KEPUASAN ANGGOTA BANK MUAMALAT TERPADU MANDIRI SEJAHTERA DI UNGARAN KAB.SEMARANG - Pradita Wahyu Eka Saputri, 13.05.51.0128 (Students' Journal of Economic and Management, 2017)
This study aims to examine the effect of product quality, service quality and price perceptions on the satisfaction of members of Bank MuamalatTerpaduMandiri Sejahtera in UngaranKab.Semarang. The population in this study are members of Bank MuamalatTerpadyMandiri Sejahtera. The number of samples studied is as many as 100 people selected as respondents by using purposive sampling technique. Data collection methods used in this study is a questionnaire filled by respondents. Data processing using SPSS Version 19. The results of this study indicate that product quality has a significant positive effect on member satisfaction, service quality has a significant positive effect on member satisfaction and price perception have a significant positive effect on member satisfaction Keywords: Product Quality, Service Quality and Price Presentment